Positive and negative affect facilitate creativity motivation: Findings on the effects of habitual mood and experimentally induced emotion - He, Wu-jing (Frontiers in Psychology, 2023)
This research involved two investigations that examined the effects of two types of affect (i.e., mood and emotion) on creativity motivation. Study 1 examined the degree to which noninduced habitual mood impacted creativity motivation in the context of a group of junior secondary school students in Hong Kong (n = 588), while Study 2 examined the effect of the experimental manipulation of emotion induction on creativity motivation in the context of a group of undergraduate students in Hong Kong (n = 653). The Chinese version of the Creativity Motivation Scale, the International Positive and Negative Affect Schedule-Short Form, and the Affect Grid were employed to assess creativity motivation, mood, and emotional states, respectively. Interesting findings were obtained. First, both studies consistently demonstrated a facilitating role of positive and negative affect in creativity motivation. Second, both studies consistently showed that the impact of positive affect on creativity motivation was stronger than that of negative affect. While previous affect-creativity research has focused predominantly on the role of affect in the cognitive components of creativity and yielded mixed results, this research adds to the literature by showing that students’ motivation to engage in creativity-related behaviors can be influenced by a broad spectrum of affective experiences (i.e., positive and negative affect, stable and enduring moods, and momentary and mutable emotions). The theoretical and educational implications of the findings are highlighted.